2015
DOI: 10.4161/2162402x.2014.992222
|View full text |Cite
|
Sign up to set email alerts
|

A phenotype from tumor stroma based on the expression of metalloproteases and their inhibitors, associated with prognosis in breast cancer

Abstract: Keywords: Breast cancer, cancer-associated fibroblast, matrix-metalloproteases, mononuclear inflammatory cell, tumor stroma Abbreviations: bFGF, fibroblast growth factor; CAF, cancer-associated fibroblast; CI, confidence interval; ECM, extracellular matrix; EGF, epidermal growth factor; EMT, epithelial-mesenchymal transition; EGF, epidermal growth factor; ER, estrogen receptor; HER2, human epidermal growth factor receptor 2; HGF, hepatocyte growth factor; IGFs, insulin growth factors; IGFBPs, IGF binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Increasing reports indicate that a complex cross-talk exists between the β-catenin pathway and other signaling molecules, and EMT-corresponding effectors 2224. In the present study, we identified the in vitro effect of β-catenin on different malignant phenotypes in U87 glioblastoma cells.…”
Section: Discussionmentioning
confidence: 80%
“…Increasing reports indicate that a complex cross-talk exists between the β-catenin pathway and other signaling molecules, and EMT-corresponding effectors 2224. In the present study, we identified the in vitro effect of β-catenin on different malignant phenotypes in U87 glioblastoma cells.…”
Section: Discussionmentioning
confidence: 80%
“…In previous studies, we have proved that tumor-in ltrating immune cells expressing high levels of MMPs had higher rate of distant metastasis development compared with tumors with MMP's low expression pro le in immune cells (6)(7)(8)(9)(10)(11). In particular, the expression of MMP11 in tumor-in ltrating immune cells, was highly associated with both, distant metastasis development and high in ammatory pro le in breast cancer (10,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 90%
“…MMP-9 is most abundantly found at the periphery in primary tumors, but within the tumor core in metastases[143,144]. The invasive front shows the highest expression of MMP-11[142,145]. The most prevalent tumor distribution of commonly studied active MMPs is illustratively represented in Figure 2, using data from the following studies [141154].…”
Section: Matrix Metalloproteinases In Cancer: Why Are They Worthwhilementioning
confidence: 99%